IDENTIFIKASI MASALAH DAN POTENSI DESA BERBASIS INDEK DESA MEMBANGUN (IDM) DI DESA GONDOWANGI KECAMATAN WAGIR KABUPATEN MALANG - hudi setyo bakti (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2018)
This study aimed to describe the state of the index-based village building (IDM) as the regulatory Permendesa number 2 in 2016. The method used by the approach of Community-Based Research conducted qualitatively. The process of data collection is done by using variables and indicators of IDM. The results showed that Gondowangi village is the village with sub-urban categories, so that the nature of the people together, not separated geographically. Gondowangi village near to the center of public services including those built by the village. Facilities and infrastructure of the village, especially related to basic services are met, the only drawback just need to optimize utilization. While the potential of that support is the availability of human resources, the village government pro-active, local wisdom which has been running such as waste management, rural economic institutions in the form of Bumdesa already running.